Didactic proposal to work on characteristics of the Mexican culture at the end of the 19th century and at the beginning of the 20th century - Lima Muñiz, Laura; Ribó Bagaría, María Eulalia (Clio. History and History Teaching, 2018)
The teaching of history has faced many challenges, in all educational levels, ranging from primary education and without generalizing can be said that extends to university education. This means that it is increasingly necessary for teachers to know about the advances in history teaching as well as school discipline. Strategies that the teacher works with students should be directed to the development of historical thinking, the use of sources and research. The proposal presented here has the purpose that elementary students work with different versions of a historical fact while exercising their reading comprehension.
Keywords: Historical thinking; Historical sources; reading comprehension